2013
DOI: 10.6002/ect.2012.0153
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional Weight Loss in a Renal Transplant Recipient: Do Not Overlook Coeliac Disease

Abstract: Unintentional weight loss in a renal transplant recipient is an important condition, requiring diagnostic search within the framework of malignancy and opportunistic infections. To the best of our knowledge, there are no data in the literature reporting underlying coeliac disease as the cause of significant weight loss after renal transplant. We report a 32-year-old woman, who complained of significant weight loss during the 3.5 years posttransplant. Diagnostic work-up revealed coeliac disease, and a gluten-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
0
1
Order By: Relevance
“…Only 1 case report has reported celiac disease as a cause of weight loss in renal transplant recipients 14 ; however, our study is the first to report celiac disease as a cause (celiac disease has been shown in 18 patients). These patients responded to gluten-free diet (data not shown).…”
Section: Discussioncontrasting
confidence: 40%
“…Only 1 case report has reported celiac disease as a cause of weight loss in renal transplant recipients 14 ; however, our study is the first to report celiac disease as a cause (celiac disease has been shown in 18 patients). These patients responded to gluten-free diet (data not shown).…”
Section: Discussioncontrasting
confidence: 40%